Peeling behavior of a thin-film on a corrugated surface. (15th May 2015) - Peng, Zhilong; Chen, Shaohua
Abstract: The peeling behavior of a thin-film perfectly adhering on a corrugated substrate is investigated theoretically. Unlike the usually adopted average method of introducing an effective adhesion energy, the effect of substrate roughness is considered directly in this paper and an accurate closed-form solution to the peel-off force under quasi-static peeling process is achieved. Comparing to the results obtained by the average method and those of a smooth substrate case shows that the peel-off force in the present model varies periodically, similar to the roughness of substrates. Furthermore, it is interesting to find that the peeling strength (defined by the maximal peel-off force) of the corrugated interface can be significantly improved with the increase of substrate roughness, while the peel-off force obtained by the average method was found to decrease monotonically or increase first and then decrease with the increasing surface roughness. Spontaneous detachment happens locally at the valley or crest of each asperity when the substrate roughness is large enough, but it does not influence the enhanced trend of the maximal peel-off force. The effect of mode-mixity dependent interface adhesion energy on the peel-off force is also considered, by which the interface peeling strength is further improved. The results in this paper should be helpful for deep understanding of the interface behavior between a film and a rough substrate and be useful for the design of film/substrate interfaces with high interface quality in nano-devices.